Kindrachuk M.V., Mishchuk O.A., Danilov A.P., Khlevna Yu.L. The interaction peculiarities and states of fric-tion surfaces of the branch-steel pairs. - Кіндрачук, М.В.; Міщук, О.О.; Данілов, А.П.; Хлєвна, Ю.Л. (Problems of Tribology, 2014)
By the methods of microprobe Auger electron spectroscopy, x-ray energy dispersive microanalysis, scanner elec-tron and optical microscopy, the conjugate micro-regions of the friction surfaces of bronze and steel were archived as in simi-lar as immediate conditions of well-known effect of the “selective transfer” of elements in friction contact zone. New data about the creation mechanism and properties of surface “served film” on the bronze were found. In particularly, the key effect of transfer of the steel carbide fragments to the branch friction surface on the mecha-nisms of creation of branch surface layers was found. It is show the phenomenon of “served film” is connected with the car-bon-copper nanomixed film which neatly localized into surface layers of branch-steel pairs. Predominantly, this “film” local-izes on the branch surface. Film thickness decreases sharply then contact temperature increase lightly as a result of friction contact zone oxidation. Simultaneously, the thickness of oxygen layer in conjugate micro-regions of steel surface increases sharply too. Copper on the ball bearing steel surface was registered as micro impurities only. Therefore, the “copper” tints of friction surfaces of the steel for the branch-steel pairs were caused by iron oxides.